Documenting, monetising and taxing Brazilian slaves in the eighteenth and nineteenth centuries - Rodrigues, Lúcia Lima (2015)
Although Brazil imported more African slaves than any other country in the Americas, knowledge of the accounting and taxation of slave-related transactions in Brazil is under-developed. We explore Portuguese-language documents showing how accounting and taxation were implicated in maintaining slavery in Brazil in the eighteenth and nineteenth centuries. The study presents examples of key documents involving slaves (such as inventory lists, rental agreements, insurance policies, and receipts) and explains how slave-related transactions were recorded and taxed. We enable important comparisons to be drawn with the accounting and taxation of slaves in the USA and British West Indies.